Strategi Guru dalam Meningkatkan Mutu Belajar Siswa di SMP Negeri 1 Pancur Batu - Amiruudin, Amiruudin; Damanik, Aulia Rahmi; Jannah, Dawi Nur; Hasibuan, Razak Hadinata; Marpaung, Jelita Ramadhani (MODELING: Jurnal Program Studi PGMI, 2023)
This research aims at strategic exploration of SMP Negeri 1 Pancur Batupada increase mutual learning. The research instrument that has run out means interviews, observation and document study. The data collected, as well as the results of the research, explain that the art of principal management in improve the quality of education at State Junior High School 1 Pancur Batu by conducting analysis internal and external analysis to find out weaknesses, strengths, opportunities as well threats exist. There are several strategic principals that are carried out on raising mutual learning namely the formation of school organizational structures, partnerships, participatory, unity and accountability. School head management art model on raising quality learning has not been fully carried out properly, singing is why there needs to be a struggle repair.